Peran Tutor dalam Meningkatkan Minat Belajar Peserta Didik Program Paket A Kelas V di SKB Mojokerto - Puteri, Izzatul Laely; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2026)
Learning interest is one of the critical factors determining the success of learning in nonformal education, particularly in equivalency programs such as Package A. In the context of nonformal educational institutions, students come from diverse social and economic backgrounds and often lack consistent motivation, making the tutor's role essential. This study aimed to: (1) describe the role of tutors in increasing students' learning interest, (2) identify supporting and inhibiting factors faced by tutors, and (3) explain the efforts undertaken by tutors to overcome obstacles and optimize the learning process at SKB Mojokerto. A qualitative descriptive approach was employed. Subjects included three tutors and eight Package A Class V students at SKB Mojokerto, selected through purposive sampling. Data were gathered during a two-month research period via observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing. Validity was ensured through source and technique triangulation. Findings revealed that tutors performed four key roles: motivator, facilitator, mentor, and evaluator. Tutors applied interactive and contextual teaching methods, delivered consistent motivational support, and created a warm, comfortable learning environment. Supporting factors included adequate facilities and positive tutor-student relationships, while inhibiting factors included students' low self-confidence, limited family support, and inconsistent attendance. The tutor's multidimensional role significantly contributed to improving learning interest among Package A students at SKB Mojokerto.